POLA KOMUNIKASI ORANG TUA TERHADAP ANAK TUNAGRAHITA - Bela Supriani (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2021)
Communication is the process of interaction in delivering messages from the communicator to the communicant. In the process of parental interaction in shaping the commendable character of mentally retarded children, special abilities are needed. One of them is by applying appropriate communication patterns with children. The purpose of this research; to find out the form of parental communication patterns in forming commendable morals in mentally retarded children, the implementation of communication patterns by parents and the obstacles of the communication patterns applied. This research uses a descriptive approach with a qualitative research type. Data was collected by using observation, interview and documentation techniques. The data analysis process consists of data reduction, data presentation, verification and conclusion drawing as well as data validity techniques, namely member checks and triangulation. The results of the study consist of, 1) The forms of communication patterns made by parents to mentally retarded children in forming commendable morals are 4, namely, primary, secondary, linear and circular communication patterns. 2) The implementation of parental communication patterns that are carried out almost every day is carrying out religious guidance such as introducing and teaching the procedures for ablution, praying using cartoon images pasted on the wall, giving advice that contains decency and religious values, introducing hijaiyah letters and telling stories. the example of the prophets. 3) The obstacle of parental communication patterns to mentally retarded children is the lack of understanding of parents in applying communication patterns, interactions and conditions that are suitable for mentally retarded children.